COMPANY FINANCIAL PERFORMANCE RATIOS: THE INFLUENCES OF THE STRUCTURE OF ASSETS, CASH HOLDING, FIRM SIZE AND INSTITUTIONAL HOLDINGS ON DEBT POLICY - Ratnawati, Aryanti; Putri, Cikal Ananda; Lusiana, Senny; Gunawan, Gunawan; Khalingga, Muhammad Ariq (Multifinance, 2024)
The purpose of this study was to test and analyze the influence of asset structure, cash holding, firm size and institutional ownership on the debt policy of food and beverage industry sub-sector companies on the IDX 2018-2021.  Research method, the type of approach in this research is a Quantitative Approach. The sample of this study was obtained using the Purposive Sampling Method, obtained as many as 19 companies in the Food and Beverage Industry Sub-Sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 Period. The analysis method used is Panel Data Regression Analysis. The results showed that partially Asset Structure has a significant positive effect on debt policy, Cash Holding hurts debt policy, Company Size has no significant positive effect on policy, Institutional Ownership has a significant positive effect on debt policy, simultaneously Asset Structure, Cash Holding, Company Size and Institutional Ownership have a significant positive effect on Debt Policy. Value, Asset Structure, Cash Holding and Institutional Ownership affect debt policy with a significance level <0.05 while company size has a significance level> 0.05, meaning that company size has no positive effect on debt policy.